"High" innovators? Marijuana legalization and regional innovation. Issue 3 (20th November 2022) - Cheng, Stephanie; Lin, Pengkai; Tan, Yinliang; Zhang, Yuchen
Abstract: The past three decades have witnessed a tremendous shift in public health policies toward marijuana legalization in the United States. Adopting the process‐based view of innovation, we hypothesize that marijuana's increased use and related consequences after its legalization affect innovators' behavior and social environment during the innovation process, which in turn impacts regional innovation. Utilizing the staggered adoption of medical marijuana laws (MMLs) by 20 states between 1996 and 2013 as a quasi‐experimental setting, we find that legalizing medical marijuana reduces the overall output of regional innovation as proxied by patents' total forward‐citation count aggregated by innovator location. Further analyses decomposing the overall output into patent quantity and quality reveal that the quantity of certain patents rises after states' medical marijuana legalization. More importantly, these analyses show that the quality of all patents, especially that of "hit" patents, deteriorates, leading to a net negative effect on the overall output. These tests further suggest that different findings concerning patent quantity and quality are related to marijuana legalization's diverse influence on innovators' individual and collaborative effectiveness during the innovation process. The decline in innovation output and quality after the adoption of MMLs is robust to the use of additional identification strategies. The evidence suggests that legalizing medical marijuana has an adverse effect on regional innovation activity.